Challenges of Halal Certification Policy for MSE Products with a Leading Food and Beverage Sector Approach: Local Government Policy Analysis - Makhtum, Ahmad; Faraby, Muhammad Ersya (Review of Islamic Economics and Finance, 2024)
Purpose – The study aims to that public policy in implementing the halal certification process massively in recently years. This study has the scope of roles as well as challenges of halal certification by local governments which have an important role in accelerating halal certification. Thus, the government can map priorities of challenges in order to alleviate various problems in the implementation of halal certification evenly in all business sectors.Methodology - The study was conducted qualitatively with descriptive analysis in several sectors of government service institutions in accordance with the main tasks of functions in Micro Small Enterprises, especially in the leading sector for food and beverages. Findings - Some of the challenges faced by local governments, especially in Micro, Small Food and Beverage Enterprises, include; availability of data on business actors, literacy of micro business actors, government socialization programs, synchronization of regulations and programs to local governments, regional budget limitations, collaboration with related parties.